Structure and function of the native and recombinant mitochondrial MRP1/MRP2 complex from Trypanosoma brucei - Zíková, Alena; Kopecná, Jana; Schumacher, Maria A; Stuart, Kenneth; Trantírek, Lukás; Lukes, Julius (International journal for parasitology, 2008)
The mitochondrial RNA-binding proteins (MRP) 1 and 2 play a regulatory role in RNA editing and putative role(s) in RNA processing in Trypanosoma brucei. Here, we report the purification of a high molecular weight protein complex consisting solely of the MRP1 and MRP2 proteins from the mitochondrion of T. brucei. The MRP1/MRP2 complex natively purified from T. brucei and the one reconstituted in Escherichia coli in vivo bind guide (g) RNAs and pre-mRNAs with dissociation constants in the nanomolar range, and efficiently promote annealing of pre-mRNAs with their cognate gRNAs. In addition, the MRP1/MRP2 complex stimulates annealing between two non-cognate RNA molecules suggesting that along with the cognate duplexes, spuriously mismatched RNA hybrids may be formed at some rate in vivo. A mechanism of catalysed annealing of gRNA/pre-mRNA by the MRP1/MRP2 complex is proposed.
Keywords: RNA Editing; Microscopy, Electron; RNA, Guide, Kinetoplastida; guide RNA, Kinetoplastida; prekurzory RNA; proteiny vázající RNA; rekombinantní proteiny; Recombinant Proteins; RNA protozoální; mitochondriální proteiny; Multidrug Resistance-Associated Proteins; elektronová mikroskopie; RNA, Protozoan; proteiny spojené s mnohočetnou rezistencí k lékům; Trypanosoma brucei brucei; Chromatography; editace RNA; RNA Precursors; RNA-Binding Proteins; Mitochondrial Proteins; chromatografie